Citation analysis of the University of the Philippines College of Dentistry Library theses with implications on collection development - Castro, Maria Nimfa V.; Apolinario, Rhea Rowena U.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
The vast flow of information has been a challenge to librarians nowadays due to technological advancements. The provision of relevant materials to meet the needs of library users is one of the responsibilities of librarians. To be able to know the relevance of a library's collection is to evaluate it.
Citation analysis is the method used to evaluate the collection of the UPCD Library which was done for the first time after its establishment in 1931. This study aims to determine the relevance of the UP College of Dentistry Library collections by examining the citation patterns of graduate and undergraduate theses from 2000-2012.
The study revealed that the distribution of theses written were more on the areas of General Oral Medicine (72 theses) and Community Dentistry (63 theses). While there were less than 36 theses written under each subject areas of Orthodontics Prosthodontics, General Operative Dentistry, Restorative Dentistry, Periodontics, Oral Surgery; and only 1 thesis each for Pedodontics and Endodontics. In some subject areas like General Oral Medicine, Orthodontics, Restorative Dentistry and Prosthodontics, it turned out that the numbers of citations are more than what the library has in its collections. While in areas of Periodontics, Surgery, Endodontics, Community Denstistry, General Operative Dentistry and Pedodontics, the number of book collection are more than the number of citations. There were books and journals cited but are not in the collection fo the UPCD Library which has to be noted and could be considered for future acquisitions of library materials. Looking for these in databases in the UP System could also be considered. However, there were those that the library keeps in its collection but did not find useful by UPCD students for their theses, at least at that time. These are the materials that may be candidates for de-selection. Most cited authors whose works had found useful were identified including Quisumbing, the only Filipino author in the list. Ten most cited journals were named and cited more than 80 to nearly 1,000 times. Lastly, there were three online journals identified to be absent in the collections of UPCD Library but available in UP Diliman and accessible in UP Manila via IP address.
Based on the outcome of the study, the following are recommended: that the journal collection of the library be maintained either in print, online or both if the budget permits and more books, as much as possible, in all subject areas be added in the collection of UPCD Library; to promote awareness and use of available resources from the libraries of Constituent Campuses (CUs) particularly those that are accessible to the whole U.P. System; that a weeding process be initiated to maintain balance of collection, provide space to the presently congested shelves, and to provide space for the growing collection; and conduct further study on how students are able to access the resources which are not available in the UPCD Library. Such study could provide for new concrete data on how to further improve the collection development efforts of the Library.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Manila). -- College of Dentistry. -- Library; Bibliographical citations; Dissertations, Academic -- Philippines -- Manila